2003
DOI: 10.1007/s00134-003-1702-6
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Influence of two different volume replacement regimens on renal function in elderly patients undergoing cardiac surgery: comparison of a new starch preparation with gelatin

Abstract: Sensitive markers of kidney dysfunction increased in our elderly patients indicating moderate alterations in kidney integrity during cardiac surgery. The two volume replacement regimens did not differ with regard to kidney integrity in elderly patients undergoing cardiac surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(45 citation statements)
references
References 30 publications
(32 reference statements)
2
42
0
1
Order By: Relevance
“…Some reports have shown that HES has no adverse infl uence on renal function in surgical patients [19,20], while other reports have shown that HES may impair renal function in surgical patients [21,22]. A recent review suggested that HES may have adverse effects on renal function, regardless of its molecular weight, DS, or C2/C6 ratio [23].…”
Section: Discussionmentioning
confidence: 96%
“…Some reports have shown that HES has no adverse infl uence on renal function in surgical patients [19,20], while other reports have shown that HES may impair renal function in surgical patients [21,22]. A recent review suggested that HES may have adverse effects on renal function, regardless of its molecular weight, DS, or C2/C6 ratio [23].…”
Section: Discussionmentioning
confidence: 96%
“…As colistin is extensively reabsorbed by renal tubular cells and causes apoptosis (18,50), urinary NGAL and NAG excretion was monitored in the present study. Under normal conditions, urinary excretion of NGAL and NAG is low, but the excretion rises sharply from the respective basal levels in response to kidney injury to reach diagnostic levels within a very short time, as much as 24 h or more before any significant rise in serum creatinine (51)(52)(53)(54)(55)(56)(57). In the current study, the rates of urinary excretion of NGAL and NAG on day 3 or 5 of colistin treatment and at the end of treatment, in all patients as well as those with AKI as defined by the RIFLE system, were significantly higher than the respective baseline values in both the colistin and the colistin-ascorbic acid groups.…”
Section: Discussionmentioning
confidence: 97%
“…However, another study found that the rise in urinary NAG is extremely sensitive to renal tubular injury and increases also in patients who do not develop clinical AKI after surgery [32,33]. Similarly, Blaikley et al [34] found RBP to rise significantly 3 h after cardiac surgery in a small study of 7 patients, but did not calculate its predictive value.…”
Section: Discussionmentioning
confidence: 99%